Controllable graphene oxide-based biocompatible hybrid interface as an anti-fibrotic coating for metallic implants. (June 2022) - Chen, Chong-You; Tsai, Pei-Hsuan; Lin, Ya-Hui; Huang, Chien-Yu; Chung, Johnson H.Y.; Chen, Guan-Yu
Abstract: In tissue engineering, foreign body reactions (FBRs) that may occur after the insertion of medical implants are a considerable challenge. Materials currently used in implants are mainly metals that are non-organic, and the lack of biocompatibility and absence of immune regulations may lead to fibrosis after long periods of implantation. Here, we introduce a highly biocompatible hybrid interface of graphene oxide (GO) and collagen type I (COL-I), where the topological nanostructure can effectively inhibit the differentiation of fibroblasts into myofibroblasts. The structure and roughness of this coating interface can be easily adjusted at the nanoscale level through changes in the GO concentration, thereby effectively inducing the polarization of macrophages to the M1 state without producing excessive amounts of pro-inflammatory factors. Compared to nanomaterials or the extracellular matrix as an anti-fibrotic interface, this hybrid bio-interface has superior mechanical strength, physical structures, and high inflammation. Evidenced by inorganic materials such as glass, titanium, and nitinol, GO-COL shows great potential for use in medical implants and cell-material interfaces. Graphical abstract: Image 1 Highlights: Graphene oxide conjugated collagen (GO-COL) composite biocompatible hybrid interface with adjustable nanoscale level structure and roughness. The 3D fibrous structure of GO-COL can effectively inhibit the differentiation of fibroblasts into myofibroblasts. The nanoscale roughness of GO-COL, coupled with the oxygen functional groups on GO, synergistically influenced the polarization of macrophages. GO-COL shows potential as a biocompatible hybrid interface for anti-fibrotic strategies when applied to common implant materials such as titanium and nitinol.